Členjenje prostorskih politik - Kos, Drago (Urbani izziv, 1997)
The aim of the text is to present the complexity of spatial policies in developed countries. Owing to the unclear distinction between horizontal and vertical levels and the dynamic changes between tiers and departments, even specialists have problems in defining and implementing spatial policies. Because of historical and contemporary transitional changes, the conditions in slovenia are even more complex. When discussing the consequences of change on the physical reality, we can expect more complications, since the number of factors influencing spatial policies is growing. Although the tradition of physical planning would stigmatise the incrementalist method of muddling through, it seems to be the most realistic possiblity.
Keywords: bivalno okolje; neformalne dejavnosti; prostor; prostor (sociologija); prostorsko planiranje; spatial planning